Zika Virus, Congenital Infection, and Neurologic Manifestations in Children: A Narrative Review - Narges Karimi; Athena Sharifi Razavi (Mazandaran University of Medical Sciences, 2017)
Context: Zika virus (ZIKV) is an arbovirus of the family Flaviviridae. This virus, which is transmitted by mosquitoes, usually affects children and causes self-limited diseases, associated with fever, maculopapular rash, conjunctivitis, arthralgia, and myalgia. There is a significant relationship between ZIKV infection and central nervous system disorders in infants. In this study, we aimed to review neurologic manifestations of ZIKV infection in infants. Evidence Acquisition: We searched the following Mesh terms in scientific databases: "Zika virus", "infants", "children", "neurologic manifestations", and "congenital infection". Electronic databases including Google Scholar, Science Direct, PubMed, Web of Science, Scientific Information Database, and Scopus were searched from 2000 to 2016. Results: The literature review showed a probable relationship between ZIKV infection and prevalence of microcephaly in newborns. Besides microcephaly, other central nervous system abnormalities included abnormal gyral arrangement, decreased brain parenchymal volume, cortical atrophy and malformation, cerebellar hypoplasia, and delayed myelination of the brain stem. Conclusions: Vertical transmission of ZIKV in pregnant women is associated with intrauterine infection and brain malformations in the developing fetus, including microcephaly, calcification, cortical displacement, ventriculomegaly, and white-matter abnormalities.